Pengaruh Job Crafting dan Learning Agility terhadap Employee Engagement (Studi pada Karyawan PT Nusantara Surya Sakti Mamuju) - Selvi Mustafa; Suwanti Suwanti; Agus Halim (STIE AMKOP, 2026)
This study aims to analyze the effect of job crafting and learning agility on employee engagement among employees of PT Nusantara Surya Sakti Mamuju. This research employs a quantitative approach with an associative method. The sample consisted of 35 employees selected using a total sampling technique. Data were collected through questionnaires supported by observation, interviews, and documentation. Data were analyzed using multiple linear regression with SPSS, including validity tests, reliability tests, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results show that job crafting has a significant partial effect on employee engagement (t-value 2.499 > t-table 2.037; sig. 0.018 < 0.05). Learning agility also has a significant partial effect on employee engagement (t-value 3.255 > t-table 2.037; sig. 0.003 < 0.05). Simultaneously, job crafting and learning agility significantly affect employee engagement (F-value 9.056 > F-table 3.295; sig. 0.001 < 0.05). The coefficient of determination (R²) of 0.361 indicates that both independent variables explain 36.1% of the variance in employee engagement, while the remaining 63.9% is influenced by other variables outside the model. These findings suggest that employee engagement can be improved by strengthening employees’ job crafting and learning agility.